2021
DOI: 10.3389/fgene.2021.701049
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Super-Enhancers and Broad H3K4me3 Domains in Pig, Human, and Mouse Tissues

Abstract: Super-enhancers (SEs) and broad H3K4me3 domains (BDs) are crucial regulators in the control of tissue identity in human and mouse. However, their features in pig remain largely unknown. In this study, by integrative computational analyses of epigenomic and transcriptomic data, we have characterized SEs and BDs in six pig tissues and analyzed their conservation in comparison with human and mouse tissues. Similar to human and mouse, pig SEs and BDs display higher tissue specificity than their typical counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, we must acknowledge that although the PorcineAI-enhancer framework performs well in practical applications, this study still has its limitations. Firstly, due to the diversity of pig breeds [ 56 ], tissue specificity [ 57 , 88 ], and developmental stages in reality, further validation and verification of the enhancer prediction capability need to be conducted under controlled conditions to ensure the reliability of the predictions. This represents the next step for model improvement, namely fine-tuning by incorporating Chip-seq-detected enhancer sequences from different breeds, tissues, and cells, expanding its applicability to more refined application scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we must acknowledge that although the PorcineAI-enhancer framework performs well in practical applications, this study still has its limitations. Firstly, due to the diversity of pig breeds [ 56 ], tissue specificity [ 57 , 88 ], and developmental stages in reality, further validation and verification of the enhancer prediction capability need to be conducted under controlled conditions to ensure the reliability of the predictions. This represents the next step for model improvement, namely fine-tuning by incorporating Chip-seq-detected enhancer sequences from different breeds, tissues, and cells, expanding its applicability to more refined application scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Although several scientists have conducted ChIP-seq experiments to explore enhancer elements in pigs [ 47 , 56 , 57 , 58 ], most of these experiments lack collaborative support from other high-throughput data and functional validation in the laboratory. This phenomenon has resulted in a limited number of reliable enhancers in pigs, with varying quality.…”
Section: Methodsmentioning
confidence: 99%
“…In a study comparing H3K4me3‐BDs and non‐broad H3K4me3 regions in pig, mouse and human they found that H3K4me3‐BDs marked cell‐type‐specific genes in the brain and adipose tissue for all three species. [ 84 ] Further investigation into pig H3K4me3‐BDs identified between 99 and 309 H3K4me3‐BDs that shared orthologous regions in human and mouse, indicating that they might be functionally conserved. Using ChIP‐seq data from hESC H1 and mESC, Kurum et al.…”
Section: Extension Of Promoter Signatures Demarcates Broad H3k4 Domainsmentioning
confidence: 99%
“…In addition, 30 shared transcription factors and BRD4 were found to be conserved activators of mammalian pluripotency-associated SEs in parallel with three pluripotency-associated SEs (SE-SOX2, SE-PIM1, and SE-FGFR1) that are highly conserved in mammals [ 95 ]. In SE conservation studies, it is probably more accurate to speak of functional conservation and/or structural conservation in regard to the pool of regulated genes both in studying the evolution of enhancers in mammals [ 96 , 97 ] and in vertebrates in general when, for example, comparing the results to zebrafish [ 98 ]. Nevertheless, the genomic distribution of zebrafish TEs and SEs differs from that of mammalian regions.…”
Section: Constitutive Super-enhancers In Different Cell Typesmentioning
confidence: 99%